Empty chairs selected poems - Liu, Xia 1961- (Graywolf Press, 2015)
"Empty Chairs is the first publication in both English translation and the Chinese original of Liu Xia, poet, artist, and wife of the imprisoned Nobel Prize recipient Liu Xiaobo. Selected from thirty years of her work, and including some of her haunting photography, this book creats a portrait of a life lived under duress, a voice in danger of being silenced, and a spirit that is shaken but so far indomitable. Liu Xia's poems are potent, acute moments of inquiry that peel back to expose the fraught complexity of an interior world. They are felt and insightful, colored through with political constraints even as they seep beyond those constraints and toward love. " ---From back cover